Pediatric timing of epinephrine doses: A systematic review. (March 2021) - Ohshimo, Shinichiro; Wang, Chih-Hung; Couto, Thomaz Bittencourt; Bingham, Robert; Mok, Yee Hui; Kleinman, Monica; Aickin, Richard; Ziegler, Carolyn; DeCaen, Allan; Atkins, Dianne L; Maconochie, Ian; Rabi, Yacov; et al.
Abstract: Aim: To evaluate the optimal timing and doses of epinephrine for Infants and children suffering in-hospital or out-of-hospital cardiac arrest. Methods: We searched Medline, EMBASE, and Cochrane Controlled Register of Trials (CENTRAL) for human randomized clinical trials and observational studies including comparative cohorts. Two investigators reviewed relevance of studies, extracted the data, conducted meta-analyses and assessed the risk of bias using the GRADE and CLARITY frameworks. Authors of the eligible studies were contacted to obtain additional data. Critically important outcomes included return of spontaneous circulation, survival to hospital discharge and survival with good neurological outcome. Results: We identified 7 observational studies suitable for meta-analysis and no randomized clinical trials. The overall certainty of evidence was very low. For the critically important outcomes, the earlier administration of epinephrine was favorable for both in-hospital and out-of-hospital cardiac arrest. Because of a limited number of eligible studies and the presence of severe confounding factors, we could not determine the optimal interval of epinephrine administration. Conclusions: Earlier administration of the first epinephrine dose could be more favorable in non-shockable pediatric cardiac arrest. The optimal interval for epinephrine administration remains unclear.